2012
DOI: 10.1158/0008-5472.can-11-3925
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Shedding May Improve Efficiencies for Delivery of Antibody-Based Anticancer Agents in Solid Tumors

Abstract: Recombinant immunotoxins (RIT) are targeted anti-cancer agents that are composed of a targeting antibody fragment and a protein toxin fragment. SS1P is a RIT that targets mesothelin on the surface of cancer cells and is being evaluated in patients with mesothelioma. Mesothelin, like many other target antigens, is shed from the cell surface. However, whether antigen shedding positively or negatively affects the delivery of RIT remains unknown. In this study, we used experimental data with SS1P to develop a math… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 29 publications
(52 reference statements)
2
53
2
Order By: Relevance
“…Third, many tumor-specific surface antigens are actively shed from cancer cells and shedding could potentially influence not only the tissue distribution of ADCs, with not only implications for safety (39)(40)(41), but also potentially the ability to permeate from tumor vessels by nature of the impact of the size of the complex (38). Shed antigen might also impact the ability of ADCs to bind their cellular targets in tumors (42,43). A QSP model can be used to integrate many of these complex, nonlinear, and unintuitive processes involved in the cellular and physiological disposition of ADCs and their components.…”
Section: Antibody Drug Conjugate (Adc) Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, many tumor-specific surface antigens are actively shed from cancer cells and shedding could potentially influence not only the tissue distribution of ADCs, with not only implications for safety (39)(40)(41), but also potentially the ability to permeate from tumor vessels by nature of the impact of the size of the complex (38). Shed antigen might also impact the ability of ADCs to bind their cellular targets in tumors (42,43). A QSP model can be used to integrate many of these complex, nonlinear, and unintuitive processes involved in the cellular and physiological disposition of ADCs and their components.…”
Section: Antibody Drug Conjugate (Adc) Platformmentioning
confidence: 99%
“…Several models have been proposed to mechanistically model ADC efficacy (43)(44)(45)(46)(47)(48)(49)(50)(51)(52), many of which have been previously reviewed (41). Mechanistic models have often been applied to investigate antibodies as a modality, although modeling studies focused on immunotoxins have also been reported (43,52).…”
Section: Antibody Drug Conjugate (Adc) Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is generally thought that targets that are shed from the cell surface should be avoided for the development of ADCs, the clinical efficacy of Kadcyla (anti-HER2-ADC; Burris et al 2011) indicates that the presence of shed extracellular domain need not rule out an otherwise-promising ADC target. Indeed, a recent study suggests that the presence of soluble antigen may be beneficial for targeting solid tumors (Pak et al 2012). …”
Section: Selection and Validation Of Tumor-associated Targets Using Omentioning
confidence: 99%
“…The other reason for the failure of the IT in clinical trials is the fact that free mesothelin in circulation competes with membrane-associated mesothelin, for the IT. Hence, there is a sequestration of the IT by the circulating mesothelin, which reduces the effective concentration of the IT available to attack the tumors [94].…”
Section: Immunotoxins Targeting Solid Tumorsmentioning
confidence: 99%